2015
DOI: 10.1002/ams2.108
|View full text |Cite
|
Sign up to set email alerts
|

Ileosigmoidal knotting, an unusual form of acute intestinal obstruction

Abstract: Aim: Ileosigmoidal knotting is an unusual form of acute intestinal obstruction characterized by closed-loop obstruction of both ileum and sigmoid colon. We present 36 cases of ileosigmoidal knotting.Methods: A retrospective analysis was designed to examine preoperative, operative, and postoperative findings of the 36 patients with ileosigmoidal knotting who were surgically treated in Necmettin Erbakan University's Meram Medical Faculty (Konya, Turkey) throughout a 26-year period.Results: The mean age was 55 (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(30 citation statements)
references
References 5 publications
6
24
0
Order By: Relevance
“…Similar to primary small bowel volvulus and sigmoid volvulus, for reasons not yet clear, ISK is predominantly a male disease. Our study, other studies from Ethiopia, and similar studies elsewhere showed a male to female ratio ranging 3 : 1 to 5 : 1 [ 1 , 3 , 6 , 10 – 12 , 15 , 18 ].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Similar to primary small bowel volvulus and sigmoid volvulus, for reasons not yet clear, ISK is predominantly a male disease. Our study, other studies from Ethiopia, and similar studies elsewhere showed a male to female ratio ranging 3 : 1 to 5 : 1 [ 1 , 3 , 6 , 10 – 12 , 15 , 18 ].…”
Section: Discussionsupporting
confidence: 87%
“…It is also common in Turkey [ 1 , 3 , 4 , 8 , 9 , 18 , 19 ]. The condition is seen in relatively young adults, and mean age ranges from 35.8 to 55 years, which is also the case in our study [ 1 , 3 , 4 , 6 – 11 , 13 , 15 ]. Similar to primary small bowel volvulus and sigmoid volvulus, for reasons not yet clear, ISK is predominantly a male disease.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations